AN ANALYSIS OF GRAMMATICAL ERRORS BY THE FIRST SEMESTER STUDENTS - Sulistyo Adi Joko Saharjo; Ni Nyoman Nidya Trianingrum (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2017)
The present study dealt with An Analysis of Grammatical Errors bythe eighth grade students of SMP Negeri 1 Kuta Utara in academic year 2016/ 2017. The researcher interested in analyzing kinds of errors because the errors were made by students should be corrected so not to become fossilized. The total amount of population which consisted of 12 classes were 384 students all together. The amount of population was determined by using quota random sampling technique. The number of representative students which used as subjet under study was 40 students. The present study which made use of an ex-post facto research design was intended to answer the following research questions: what kind of grammatical errors which is made by the eighth grade students of SMP Negeri 1 Kuta Utara in academic year 2016/ 2017 in constructing direct and indirect speech. The data required for the study were collected by using grammatical transformation tasks. In the grammatical transformation tasks, the students were asked to change direct speech to indirect speech or vice versa by the correct grammatical forms in the sentences. The result revealed that there were 303 errors made by the students. From the total number of students’ errors, the researcher found that there were four types of errors. There were 43(14,19%)of omission error, there were 29(9,57%)of addition errors, there were 58(19,14%)of malformation errors, and there were 173(57,09%)of disordering errors. The finding of present study was many students who weredifficultto answerdirect and indirect speech. They lacked of knowledge and inability in mastering English grammar so many mistakes were made by them.